ASSESSMENT INNATE IMMUNE RESPONSE IN INFANTS WITH GENERALIZED HERPES INFECTION - A. Y. Levkovich; A. A. Afonin; M. A. Levkovich; L. V. Kravchenko (Медицинский вестник Юга России, 2013)
Purpose: Identification of new pathogenic mechanisms of generalized herpes infection in newborn infants.Materials and Methods: A clinical and laboratory examination of 48 infants in the early neonatal period. In 22 children (study group), there was a generalized herpes infection. The control group consisted of 26 clinically healthy newborns. The content of pro-and anti-inflammatory cytokines and chemokines (IFN-γ, IFN-α, IL-12, IL-4, MCP- 1) expression of TLR-2 on monocytes of peripheral blood, frequency polymorphism of Arg753Gln TLR-2 gene.Results: Found that the criterion of herpes generalized infection is reduced number of monocytes expressing TLR-2 gene polymorphism Arg753Gln TLR-2, which is associated with a reduced content of IFN-α, IL-12 and IFN-y in the serum.Summary: The development of generalized herpes infection in newborns occurs against violations of the mechanisms of the innate immune response.